The Impact of Inclusive Work Environment on the Performance of Employees with Disabilities - Wursan (Smart International Management Journal, 2025)
This study examines the impact of an inclusive work environment on the job performance of employees with disabilities in formal companies in DKI Jakarta and West Java, Indonesia. Using a quantitative cross-sectional design, the study analyzes key dimensions of inclusiveness—reasonable accommodation, inclusive organizational culture, and managerial and peer support—and their influence on performance. Data from 312 employees with disabilities working in companies with Disability Service Units or inclusive policies were analyzed using multiple linear regression. The results show that the model significantly predicts job performance, explaining 21.8% of the variance. Inclusive organizational culture had the strongest positive effect, followed by managerial and peer support, while reasonable accommodation showed a smaller but still significant impact. These findings emphasize that fostering an inclusive organizational culture and providing psychosocial support are more critical for enhancing employee performance than focusing solely on physical accommodations. The study supports the Social Model of Disability by highlighting the importance of removing environmental and social barriers in the workplace. Accordingly, the study recommends strengthening inclusive organizational culture and leadership practices to achieve equitable employment outcomes for persons with disabilities.